Analysis of reading comprehension skills among elementary school students: What should professional teachers do? - Maryani; Reva Maria Valianti; Liza Murniviyanti; Arizona; Saden Nunyuli Amedome; M. Khoirudin Jalil (Journal of Professional Teacher Education, 2026)
Reading comprehension is a fundamental skill for academic success in elementary school, yet many students continue to struggle to understand text content, particularly at the fourth-grade level. While prior studies have examined reading comprehension broadly across elementary grades, few have combined test, observation, and interview data to build a context-specific profile of a single fourth-grade cohort. This study addresses that gap by analyzing the reading comprehension skills of fourth-grade students at SDN 106 Palembang, a public elementary school in Palembang, South Sumatra, Indonesia, and identifying the factors associated with their performance. Using a qualitative descriptive design supported by a reading comprehension test, data were collected from 30 fourth-grade students through tests, classroom observations, and teacher interviews. The findings show that students' reading comprehension remains at a moderate-to-low level: many students had difficulty identifying main ideas, summarizing or drawing conclusions from text, and interpreting implied meaning, and a majority showed low engagement during reading activities. These difficulties appear to be associated with internal factors (limited reading interest, motivation, and vocabulary) and external factors (limited variety in teaching methods and learning media). The study contributes context-specific, triangulated evidence on fourth-grade reading comprehension and highlights the need for elementary teachers to implement more interactive, varied, and media-supported reading instruction to strengthen students’ comprehension skills and engagement.